2023
DOI: 10.3340/jkns.2022.0200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adjunctive Tranexamic Acid in Facilitating Resolution of Chronic Subdural Hematoma after Surgery

Abstract: Objective : Chronic subdural hematoma (CSDH) is a common neurosurgical disease and generally treated with burr-hole surgery alone. Tranexamic acid (TXA) is an antifibrinolytic agent that potentially reduces recurrence rates and the residual hematoma volume. However, the role of postoperative TXA medication remains unclear to date. This study aimed to verify the effectiveness of adjunctive TXA in the view of early hematoma resolution.Methods : Between January 2018 and September 2021, patients with CSDH who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Since then, other studies have pointed divergent results. Yang et al 15 presented animating results in their sample, while Yamada et al 25 carried out a randomized clinical trial with a treatment protocol similar to the one in this study and found no bene t from tranexamic acid in terms of recurrence avoidance 25 .…”
Section: Generalizationmentioning
confidence: 67%
See 2 more Smart Citations
“…Since then, other studies have pointed divergent results. Yang et al 15 presented animating results in their sample, while Yamada et al 25 carried out a randomized clinical trial with a treatment protocol similar to the one in this study and found no bene t from tranexamic acid in terms of recurrence avoidance 25 .…”
Section: Generalizationmentioning
confidence: 67%
“…When patients have normal conscience status, no motor de cits, and/or controlled symptoms like seizures or headache some nonsurgical treatments are being tried. There have been growing reports on the use of statins (HMG-CoA reductase inhibitors) [21][22][23][24] , tranexamic acid [12][13][14][15]25 (antiplasminogen anti brinolytic), a platelet-activating factor receptor antagonist (etizolam) 26,27 , angiotensin-converting enzyme inhibitors 28-30 , corticosteroids [31][32][33][34][35] , goreisan 13,25,36,37 and antiangiogenic endovascular procedures like embolization of the distal middle meningeal artery (MMA) [38][39][40][41][42][43] . All medications used until now share a potential role on in ammatory processes underlying CSDH formation.…”
Section: Generalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been growing reports on the use of statins (HMG-CoA reductase inhibitors) [21][22][23][24], tranexamic acid [12][13][14][15]25] (antiplasminogen antifibrinolytic), a platelet-activating factor receptor antagonist (etizolam) [26,27], angiotensin-converting enzyme inhibitors [28][29][30], corticosteroids [31][32][33][34][35], goreisan [13,25,36,37], and antiangiogenic endovascular procedures like embolization of the distal middle meningeal artery (MMA) [38][39][40][41][42][43]. All medications used until now share a potential role on inflammatory processes underlying CSDH formation.…”
Section: Generalizationmentioning
confidence: 99%
“…Trans-4-(aminomethyl)cyclohexane-1-carboxylic acid, also known as tranexamic acid (TXA), induces anti-fibrinolysis, and it is believed that it may promote hemostasis in microbleeding [12]. There are reports of reduction in recurrence rate with the use of TXA in the postoperative period [13][14][15]. We conducted a prospective, randomized, controlled study to determine whether the postoperative use of oral tranexamic acid reduces the risk of recurrence after CSDH treatment by burr-hole and to evaluate any associated complications.…”
Section: Introductionmentioning
confidence: 99%